Analisa dan Perancangan Optimasi Jaringan dengan Metode Wireles Distribution System - Sidik Rohmanto; Saiful Bahri; Wisnu Sanjaya (JITU : Journal Informatic Technology And Communication, 2022)
designing an internet network that utilizes wireless lines to expand the network area coverage that is able to cover the entire area of ​​the Walen Village Office building is the goal of the research. The internet network design that the researcher uses is a network design with a WDS wireless distribution system model. The results of the design of the internet network with the WDS (Wireless distribution system) model will be tested for 7 days with 3 tests every day, namely 07.00-08.00 "morning", 12.00-13.00 "noon", 16.00-17.00 "afternoon". Network testing is carried out with the aim of finding the QoS (Quality of Service) value of the network that the researcher has implemented at the Walen Village government office, Simo District, Boyolali Regency, the testing procedure that the researcher does is by observing the network during testing with the help of the "wireshark" application. The test results showed that the total average of all the parameters tested during the observation showed satisfactory results with an index value of 3.3 in the satisfactory category.